Impact of COVID-19 Social Distancing Restrictions on Training Habits, Injury, and Care Seeking Behavior in Youth Long-Distance Runners - Bazett-Jones, David M.; Garcia, Micah C.; Taylor-Haas, Jeffrey A.; Long, Jason T.; Rauh, Mitchell J.; Paterno, Mark V.; Ford, Kevin R. (Frontiers in Sports and Active Living, 2020)
Purpose: The COVID-19 pandemic impacted the sporting and exercise activities of millions of youth. Running is an activity that could be maintained while social distancing restrictions were implemented during the pandemic. If running-related injuries do occur, these restrictions may also influence the access to care or care seeking behavior of this population. Therefore, the purpose of this study was to determine if the social distancing restrictions during the 2020 COVID-19 pandemic influenced training habits, injury, and care seeking behavior in youth long-distance runners. Methods: A customized, open online questionnaire was provided to runners 9–19 years of age who participated in long-distance running activities including team/club cross-country, track and field (distances ≥800 m), road races, or recreational running. Participants responded to questions about demographics, running habits, RRIs, and health care provider visits 6-months before as well as during social distancing restrictions due to COVID-19. Wilcoxon signed rank tests compared differences for ratio data and Chi-square tests were used to compare proportions before and during COVID-19 social distancing restrictions. Statistical significance was set at p ≤ 0.05. Results: A total of 287 youth long-distance runners (male = 124, female = 162, unspecified = 1; age = 15.3 ± 1.7 years; running experience = 5.0 ± 2.3 years) participated. Compared to their pre-COVID-19 responses, youth long-distance runners reported lower distances run per week (p < 0.001), fewer runs per week (p < 0.001), fewer hard runs per week (p < 0.001), fewer number of injuries (p < 0.001), and fewer injuries per 1,000 km (p = 0.002) during the COVID-19 social distancing restrictions. A lower proportion of participants reported in-person health care provider visits (p < 0.001) and a lower proportion of visits were made to an athletic trainer during COVID-19 social distancing restrictions compared to prior to COVID-19 (p < 0.001). Conclusion: The COVID-19 pandemic resulted in significant decreases in both training and injuries which were different compared to previous reports in an adult population. Many of the runners who sustained an injury during COVID-19 social distancing restrictions did not seek care, with the most prominent reduction in visits to an athletic trainer. This could impact future injury and chronic pain.